THE ROLE OF ANONYMITY IN ARTIFICIAL INTELLIGENCE BASED CHATBOT USAGE BY UNIVERSITY STUDENT AT MEDAN - Randy Brilliant Chandra; Erwin Setiawan Panjaitan; Muhammad Fermi Pasha; Thamrin Thamrin; Robin Robin (Program Studi Teknik Informatika Universitas Khairun, 2025)
AI Chatbot is a computer program integrated with artificial intelligence designed to interact with humans and provide useful information. AI Chatbot offers anonymity, one of the factors motivating someone to use it since they feel safe. Indonesian students nowadays inhibit shyness to ask questions and participate in learning due to anxiety factors and fear of negative judgment. Therefore, it is necessary to conduct a test to understand the extent of acceptance factors of AI Chatbots. This research aims to examine the effect of anonymity variable on the use of AI Chatbots among university students at Medan using the UTAUT2 model. A survey was conducted on 421 students. Using the Structural Equation Modeling (SEM) model with the help of SmartPLS software, this study introduces the anonymity variable in the UTAUT2 model, which has a positive and significant effect on students’ behavioral intention to use AI Chatbots. These findings also show that price value and habit have a positive and significant effect on behavioral intention, also habit and behavioral intention effect students’ behavior towards AI Chatbots at Medan. However, performance expectancy, effort expectancy, social influence, facilitating conditions, and hedonic motivation do not affect the students’ behavioral intention and behavior towards AI Chatbots